Democracy, Governance and Civil Society in South Asia (The Distinguishedl Lecture) (The Pakistan Development Review, 1994)
Six years ago, at the start of 1988, the prospect for democracy in South Asia did not appear very promising. The military rulers both in Pakistan and Bangladesh had managed to cloak their regimes in civilian attire and appeared well entrenched even if their quest for legitimacy had evaded them. In Nepal and Bhutan the hereditary monarchs showed no signs of conceding to the demands for popular participation despite the simmering political discontent in both countries. The democratic traditions of Sri Lanka had proved sufficiently resilient for the formal representative institutions to endure but the continued civil strife and violence had virtually reduced effective popular participation into a farce. Likewise in India, whilst the ghost of Indira Gandhi's authoritarian rule during the emergency in 1975-77 had been exorcised by subsequent renewals of popular mandate, the democratic institutions and popular accountability had probably suffered irreversible damages and it was not uncommon amongst political analysts to speak of the 'ungovernability' of the country.